Pathogenicity of Clostridium perfringens Philippine Isolate in Necrotic Enteritis Across Broiler Growth Stages - Racho, Ma. Rosario S.; Purnamasari, Listya; Olarve, Joseph P.; Rovira, Hope G.; dela Cruz, Joseph Flores (Jurnal Medik Veteriner, 2025)
Clostridium perfringens was isolated from Philippines broiler chickens of a local farm exhibiting clinical signs of necrotic enteritis. This local isolate induced necrotic enteritis (NE) experimentally in susceptible broiler chickens to demonstrate the disease and the lesions it would produce. Experimental chickens were subjected to stress such as vaccination and pathogenic Escherichia coli and Salmonella enteritidis. Seven treatment groups involving various combinations of the above agents were used to demonstrate lesions of NE. Gross intestinal lesion scoring was performed at necropsy on the 3rd, 7th, 11th, 14th, and 18th-day post-infection, depending on the treatment group. Results showed that the local C. perfringens isolate was able to cause lesions of enteritis but did not demonstrate the classic towel-like lesion of NE, as described by the literature. The treatment combination of C. perfringens and S. enteritidis produced the highest intestinal lesions scores. However, C. perfringens alone can experimentally induce enteritis with a lesser severity. This is the first report of experimental induction of NE in broiler chickens using a local C. perfringens isolate in the Philippines.